Aquinas, Education and the East
XIV, 198 p.
Keywords: A confluence of scholarly interest has resulted in a revival of Thomistic scholarship across the world. Several areas in the investigation of St. Thomas Aquinas, however, remain under-explored. This volume contributes to two of these neglected areas. First, the volume evaluates the contemporary relevance of St. Thomas's views for the philosophy and practice of education. The second area explored involves the intersections of the Angelic Doctor’s thought and the numerous cultures and intellectual traditions of the East. Contributors to this section examine the reception, creative appropriation, and various points of convergence between St. Thomas and the East.